Principal's Leadership Role in Improving Teacher Competence - Septi Wahyu Estiani; Enung Hasanah (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2022)
Teacher Professional Competence refers to the ability or competence needed to complete the responsibilities of a teacher correctly. Every teacher must-have skills that will enable them to carry out their professional duties. Teachers play an essential role in efforts to achieve national education goals. This study aims to reveal the role of school principals in improving teacher competence. The method used in this research is qualitative with a case study approach. The research procedure uses Miles and Huberman. Data collection techniques using interviews. Data analysis was carried out with the help of Atlas.ti software version 8. The results of this study indicate that regular supervision, increasing ethical teacher responsibilities, and developing the moral integrity of teachers are all ways to improve teacher quality. Meanwhile, school principals provide an understanding of how to understand the character of their students and encourage teachers to participate in training related to learning development and learning evaluation to improve pedagogic competence.